Current Concepts in the Treatment of Gouty Arthritis - Fang, Zhen‐hua (Orthop Surg, 2013)
Gouty arthritis is an extremely painful condition that causes functional impairment. Gouty arthritis has become increasingly complex because of multiple comorbidities, iatrogenic factors and hyperuricemia that is refractory to treatment. In this review, we present a general overview of gouty arthritis including its pathophysiology, clinical presentations, diagnosis, predisposing factors and prophylactic therapy for preventing gouty arthritis flares.